God's Necessity on Anselmian Theistic Genuine Modal Realism - Collier, Matthew James (Sophia, 2019)
On Anselmian theism (AT), God is, amongst other things, a necessary being. On genuine modal realism (GMR), possible worlds are maximal mereological sums of spatiotemporally connected individuals. I argue in this paper that AT and GMR are either incompatible or their conjunction leads to—amongst other things—modal collapse. Specifically, I argue: regardless of whether God is concrete or abstract, His necessary existence either is inconsistent with AT-GMR or it leads to, amongst other things, modal collapse for AT-GMR. I conclude the paper by contending that, if I am correct, the ATist will have an argument against the truth of GMR, and the GMRist will have an argument against the truth of AT.